Extinction studies in focus: Reflections on photography at a time of ecological decline - Kate Simpson; Sarah Oakes; Aureja Stirbyte; Katie Prosser; Timothy M. Brown; Jonathan David Roberts; Amy J. Bartlett (Cambridge Prisms: Extinction, 2025)
Through compositional inclusion or exclusion, the photograph can assert and communicate what belongs in a picture, in a landscape, in an ecosystem. It can illuminate what we deem conservation-worthy, or, on a larger scale, which extinctions are attention-worthy. Photographic practice helps to illuminate the active nature of extinction, and our choices as actors and witnesses within that process. Here, researchers from the University of Leeds’ Extinction Studies Doctoral Training Programme present individual reflections on interdisciplinary practice-led research in the Scottish Small Isles. We consider how photography, as a form of praxis, can generate new forms of knowledge surrounding extinction: its meanings, representations, and legacies, particularly through visual representation. We offer seven perspectives on contemporary image-making, from disciplines including philosophy, conservation biology, literature, sociology, geology, cultural anthropology, and palaeontology. Researchers gathered experiential, ethical, even biological meanings from considering what to include or exclude in images: from the micro to the macro, the visible to the invisible, the aesthetic to the ecological. We draw conclusions around meaning-making through the process of photography itself, and the tensions encountered through framing and decision-making in a time of mass ecological decline.